ANALISIS KEBUTUHAN UNTUK PENINGKATAN USAHA PETERNAKAN SAPI PERAH DI KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - T. Dalmiyatun; W. Roessali; W. Sumekar; D. Mardiningsih (Universitas Sebelas Maret, 2015)
This research aimed to study the needs of members of farmers District East Ungaran Semarang Regency for the development of their farming. This research analyzed descriptively by using the approach of PRA (Participatory Rural Appraisal) approach, with the techniques of thematic mapping, trends and changes, seasonal calendar, daily routine, livelihood analysis and Venn Diagram on dairy farmers.Results from the application of each single technique then was discussed in Focused Group Discussion (FGD) attended by village officers and extension worker. The results of the study can be contained in rank as follows: 1) The activities carried out by members of dairy farmer groups is still traditional. Technologies of seed selection,feed, milking, harvest and post-harvest has not been much progress, yet, 2) Limited knowledge and access to sources of technology, resources, and capital and programs for both private and government 3) Limitation of production facilities and infrastructure, which resulted in small-scale livestock ownership with inadequate productivity, and 4) Limited mastery of market information, both for sale of the products and purchase of the production factors.